Fluorinated steroids do not improve outcome of isolated atrioventricular block. (15th December 2016) - Van den Berg, N.W.E.; Slieker, M.G.; van Beynum, I.M.; Bilardo, C.M.; de Bruijn, D.; Clur, S.A.; Cornette, J.M.J.; Frohn-Mulder, I.M.E.; Haak, M.C.; van Loo-Maurus, K.E.H.; Manten, G.T.R.; Rackowitz, A.B.M.H.; et al.
Abstract: Introduction: Congenital atrioventricular block (CAVB) is a rare disorder with a significant morbidity and mortality. Consensus regarding the prescription and efficacy of prenatal corticosteroids is lacking. This nationwide study was initiated to evaluate the effects of prenatal treatment with corticosteroids on the outcome of CAVB in The Netherlands. Methods: All fetuses identified with isolated congenital AVB-II° or AVB-III° in any of the eight academic fetal heart centers of The Netherlands between 2003 and 2013 were included and reviewed. Results: Fifty-six fetuses were included. Fourteen (25%) fetuses were treated with dexamethasone. We found no differences between the steroid-treated and untreated cases regarding in utero progression of the AVB (63% vs 67% respectively), survival to birth (86% vs 84%), pacemaker implantations (74% vs 58%) or long-term dilated cardiomyopathy (13% vs 17%). Steroid treated fetuses demonstrated more in utero growth restriction (38% vs 11%). Conclusion: No benefit from prenatal corticosteroid treatment was demonstrated for fetuses with isolated CAVB in this study. However, we found negative side effects. Our data provide no evidence to support the routine administration of corticosteroids for the treatment of fetal CAVB.